Prevalence of Nosemosis and Varroosis in Honey Bees in Sinop Province - Yaman, Mustafa; Güvendik, Tuğba Sağlam; Ünal, Sabri (Kastamonu University, 2023)
Aim of study: Sinop province has a potential to progress in beekeeping. In this study, it was aimed to investigate the presence and distribution of nosemosis and varroosis in honey bees in Sinop province.
Area of study: 12 villages from 7 districts (Ayancık, Boyabat, Dikmen, Durağan, Erfelek, Gerze and Saraydüzü) in Sinop province were determined as study area.
Material and methods: A total of 874 adult bee samples were dissected in Ringer’s solution and examined for nosemosis. A total of 1.640 adult bee samples were examined for varroosis.
Main results: Nosemosis was the most common disease. Average of the nosemosis infection was 7.6%. On the other hand, varroosis was observed in the eight of 12 localities examined in Sinop province. Total infestation ranged from 0.6 to 8.2%.
Highlights: Nosemosis and varroosis were observed in eight (66.7%) of the 12 examined localities in Sinop province. These data are considered as proof that honey production is negatively affected. This study also confirms that the beekeepers in the Sinop province should be informed in detail about the precautions to be taken in the monitoring and controlling varroosis and nosemosis
Keywords: Honey Bee; Bal Arısı; Sinop; Turkey; Nosemosis; Varroosis